Book review Malachi (historical commentary on the Old Testament) - R. Kessler (Acta Theologica)
From text: Fanie Snyman, from the University of the Free State in Bloemfontein, South Africa, is one of the best known researchers in the field of Old Testament prophecy. He published articles on Jeremiah and on some of the so-called Minor Prophets, viz. Amos, Obadiah, Habakkuk, and Zephaniah. The bulk of his studies in this area, however, explore Malachi.